2005
DOI: 10.1139/l05-041
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of alkalis on the slag cement systems

Abstract: The replacement of natural materials by industrial by-products has given a variety of new construction materials that are economically viable and ecologically beneficial. Blast furnace slag is one of these industrial by-products. Its beneficial proprieties and characteristics have led to rapid growth of production in Algeria and worldwide. This research deals with the effect of alkaline activation of slag cement with clinker. Various agents that activate the process were used for testing, and it showed that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Recently it has been demonstrated by Zeghichi et al (2005) that the compressive strength of a mortar containing 80% slag, 20% cement using sodium hydroxide activator was around 11 N/mm 2 at 7 days, which is comparable with the results of the present study using clay in mortar. These findings also agree with results reported by other authors (Dai and Cheng, 1988;Shi, 1996) indicating that the strength obtained with sodium hydroxide activation was very low.…”
Section: Chemical Activationsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently it has been demonstrated by Zeghichi et al (2005) that the compressive strength of a mortar containing 80% slag, 20% cement using sodium hydroxide activator was around 11 N/mm 2 at 7 days, which is comparable with the results of the present study using clay in mortar. These findings also agree with results reported by other authors (Dai and Cheng, 1988;Shi, 1996) indicating that the strength obtained with sodium hydroxide activation was very low.…”
Section: Chemical Activationsupporting
confidence: 91%
“…At early age the strength of clay mortar containing sodium hydroxide was less than 30% of that of cement mortar. It was found that the strength of the alkali activator has a greater impact on the strength of the clay-cement system (Zeghichi et al, 2005) This fact may explain the low strength obtained in this study.…”
Section: Mechanical Activationmentioning
confidence: 51%
“…The blast furnace slag is a by-product of iron ore processing obtained from plant for steel manufacturing located in Annaba (North-East Algeria) (Kellouche et al, 2010;Zeghichi et al, 2005). Its chemical composition is also presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The curing temperature has a significant impact on the hydration of blast furnace slag [9]. Zeghichi et al [10] investigated the effect of the alkaline activation of slag cement with clinker. The results showed that alkaline activators accelerate hydration and stimulate the hardening process.…”
Section: Introductionmentioning
confidence: 99%